Antibacterial activity of locally isolated thermophilic fungi - Abdul Karim, Akmal Hayat (2015)
Sampling of thermophilic fungi was done at Cherana Puteh Hot Springs in Alor Gajah, Melaka. Isolation was done and two pure cultures were obtained named CP1 and CP2. Then, it was incubated at three different ranges of temperature to determine the best temperature of fungal growth. After that, the growth profiles of isolated thermophilic fungi was measured based on their dry cell weight. The stationary phase growths of thermophilic fungi were determined. For the screening of antibacterial properties, the secondary metabolites of thermophilic fungal secondary metabolites were extracted using methanol. The methanolic mixtures were filtered to separate the filtrate and mycelium. The crude extracts were screened for antibacterial activity against some clinical strains of test microorganisms. The test microorganisms were Escherichia coli ATCC 8739, Escherichia coli H7 ATCC E187, Staphylococcus aureus ATCC 6538, Pseudomonas aeruginosa ATCC 15442, Bacillus subtilis ATCC 6633, Salmonella typhimurium S836, Methicillin-resistant Staphylococcus aureus S547, and Listeria monocytogenes L10. Disc diffusion method was conducted to screen for the antibacterial properties that produced by the isolates against stated test microorganisms.